Terapi Fobia Matematika Menggunakan Multimedia “Digimonica” di SMA Islam Hasyim Asy’ari Batu - Ainur Rosikin; Yoga Klody Arianto; Nanda Amaliah Pramawanda; Abdul Halim Fathani (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2020)
The purpose of this study is to help students who experience mathematical phobia by conducting mathematical therapy. Mathematical therapy was carried out using multimedia